Studies on dielectric spectroscopy of oxidatively degraded Poly(α-olefin) - Iwase, Shunsuke; Maruyama, Taisuke; Momozono, Satoshi; Maegawa, Satoru; Itoigawa, Fumihiro (Frontiers in Mechanical Engineering, 2024)
Failures in tribological components such as bearings can significantly affect the performance and lifespan of machinery, necessitating the implementation of effective condition monitoring technologies. This study verified the feasibility of dielectric spectroscopy (DES) as a method for detecting abnormalities before damage occurs. A comparative evaluation was conducted between dielectric relaxation parameters and measurements from size exclusion chromatography, total acid number, and viscosity for oxidatively degraded poly (α-olefin) oils. The results confirmed that DES is an effective method for assessing the oxidative degradation state of lubricants. These findings suggest that DES could be applied to oil film condition monitoring and predictive maintenance.